Pengaruh Akuntabilitas, Kepemimpinan dan Transparansi terhadap Efektivitas Pengelolaan Dana Desa di Kabupaten Tanah Datar - Rizal, Kevin Wahyu; Sari, Vita Fitria (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to determine the influence of accountability, leadership and transparency on the effectiveness of village fund management (Case Study in Nagari Government in North Lintau Buo District, Lintau Buo District, Sungayang District, Lima Kaum District, and Pariangan District). This research uses subject data. The sampling technique used the total sampling method with a total sample of 25 villages. Data analysis uses multiple linear regression analysis. The results of the research show that accountability, leadership and transparency have a positive and significant effect on the effectiveness of village fund management in the Nagari government of Tanah Datar agency.